Forehand Smash Badminton Training Models For U-13 And U-15 Athletes - Denatara, Eskar Tri (Journal Coaching Education Sports, 2024)
Purpose – This research aims to provide variation of training and improve the results of smash badminton training especially smash accuracy. Design/methodology/approach – This research is research and development using the Borg and Gall model. The research site is at PB Jaya Raya Metland Jakarta with test models and test instruments in several clubs in the city and Bekasi district. Findings – There are three types of training models developed: footwork and shadow smash, plyometric and drill training models, and game patterns and situation models using Denatara BISA (Badminton Integrated Smash Accuracy) Smash Training Model.Research limitations/implications – The focus of this research is on the urgency of occurring minimal variation of the smash training model for athletes U-13 (age 11-12 years) and U-15 (age 13-14 years) according to the division of age groups listed in the PP PBSI regulations.Practical implications – With implications on the variable training model combined with technology-based test instruments can drive athletes in smash practice and can improve the results of smash training especially its accuracy.Originality/value – This research is relevant to the National Research Master Plan (RIRIN) related to the application of technological innovation especially in the field of education and sports.